Design of a Novel Mid-Infrared Single-Polarization Single-Mode Photonic Crystal Fiber with Low Loss, High Nonlinearity, and Large Bandwidth. Issue 2 (4th March 2019) - Hui, Zhanqiang; Hou, Dongyang; Zhang, Youkun; Wei, Shixiu; Xu, Junhua
ABSTRACT: A novel mid-infrared Ge20 Sb15 Se65 chalcogenide-based single-polarization single-mode (SPSM) photonic crystal fiber (PCF) with rectangular latticed circular air holes is proposed. The properties of SPSM bandwidth, confinement loss, and nonlinearity are analyzed in the 3 μm 8 μm mid-infrared region using the finite -difference time-domain (FDTD) method. The influences of different geometrical parameters on the properties of SPSM-PCF are analyzed. All numerical computational results reveal that for the optimized geometrical parameters, the proposed PCF can deliver a SPSM region of more than 2.3814 μm with high nonlinearity of 3, 705 w −1 km −1 . Therefore, such a SPSM-PCF will become an excellent candidate for mid-infrared photonic.